Tratamiento de la información científica divulgada por los medios El Comercio y El Universo en su edición impresa entre enero y diciembre del 2022 - Torres Medina, Allison Michelle (2024)
Science journalism is an area little studied by researchers in the field of communication, but its relevance is fundamental for the dissemination of science and its objectivity. The identification of areas or research nuclei that need to be examined is highlighted, contributing to the evolution of knowledge and outlining possible ways for the scientific community to investigate these topics. Among the objectives of the project, we sought to analyze the treatment of information on research in the media El Universo and El Comercio in their printed edition of the year 2022. For the selection of these national media, it was pertinent to identify the media with the largest audience as indicated by the SCImago Media Ranking page. According to the methodological process applied in the study, it was of a descriptive-explanatory nature, with a non-experimental design and quantitative approach, which contributed to the collection of data and informative mechanisms under the perspective of the authors Manuel Calvo and Clarena Muñoz. In order to generate significant results, in terms of data collection instruments, a non-participatory observation form and a content analysis form were applied, which allowed identifying, describing and analyzing in detail the scientific notes disclosed in the media. The results show the lack of adequate implementation of scientific dissemination mechanisms according to the news published by the national media El Universo and El Comercio. Finally, conclusions and recommendations for improvement in scientific content are presented for the selected national media according to the page ranking. Keywords: science popularization; science journalism; science communication; print media.